The Awareness and Attitude of Contracted Service Among General Medical Practitioners in Community Health Service Centers in Urban China: A Cross-Sectional Study - Yin, Tao; Yin, Delu; He, Huijing; Zheng, Xiaoguo; Li, Ruili; Yang, Huimin; Wang, Lihong; Chen, Bowen (Frontiers in Public Health, 2021)
This study aims to explore the attitude, willingness, and satisfaction with contract service (CS) among staff in community health service (CHS) centers in urban China, and explore the associated factors of satisfaction with CS. From Aug 2016 to July 2017, five CHS centers in three provinces of China were selected. Setting-level information were collected by official documents review, and personal information on demographic characteristics, awareness and attitude of CS among staff were collected by questionnaire survey. Univariate and multivariable logistic regression models were fitted to explore the associated factors of satisfaction with CS. Multiple correspondence analysis (MCA) was used to visually demonstrate the correlations among category data related with satisfaction with CS. The CS signing rate were 30.78%, 12.72%, 22.20%, 14.32%, and 21.19%, respectively, in the five CHS centers. A total of 286 staff included family doctors (40.91%), nurses (31.12%), and others (27.97%) completed the survey. For the sense of self-worth, 86.01% (246/286) staff hold a positive attitude. The predominant barrier of CS signing was caused by the work pressure due to CS performance assessment (48.60%, 139/286). About 30% of family doctors and nurses reported a heavy work pressure and more than 30% of doctors have great feeling of fatigue. Notably, 51.69% family doctors would like to change their job in the future. Comparing with other staff, family doctors were more likely to be unsatisfied with CS (OR: 2.793, 95% CI: 1.155-6.754, p=0.022). Participants in Sichuan province have lower satisfaction than other places. Work pressure and feeling of fatigue was found to be negatively associated with satisfaction of CS in the univariate regression model, but after adjusted for study areas and other covariates in the multivariable regression model, these two factors lost their statistical significance. The MCA analysis yielded similar factors consistent with multivariable results that clustering with different level of CS satisfaction. Our study revealed that the CS coverage and satisfaction among staff from primary health care system varied geographically and are associated with workload and pressure. Measures aim to promote the stability of primary care human resource should be considered in the future.